In situ incorporation of heparin/bivalirudin into a phytic acid coating on biodegradable magnesium with improved anticorrosion and biocompatible properties. Issue 22 (17th May 2017) - Chen, Yingqi; Zhang, Xuan; Zhao, Sheng; Maitz, Manfred F.; Zhang, Wentai; Yang, Su; Mao, Jinlong; Huang, Nan; Wan, Guojiang
Abstract : Drugs were incorporated into a phytic acid coating on Mg by an in situ chemical route for corrosion control and biocompatibility. Abstract : Heparin (Hep) or bivalirudin (BVLD) were immobilized in an organic phytic acid (PA) coating on Mg by an in situ chemical route. Such a drug-loaded PA coating was designed to enhance both corrosion control and biocompatibility. It was found that both Hep- and BVLD-loaded PA coatings exhibited a dual role in effectively controlling corrosion as well as providing a biofunctional effect. Experiments involving electrochemical corrosion and in vitro degradation by immersion revealed that PA&Hep- and PA&BVLD-coated Mg had the same effect or even slower corrosion/degradation in phosphate buffered saline compared to PA-coated Mg, and it degraded significantly slower than untreated Mg. Moreover, Hep- or BVLD-loaded PA coatings showed relatively good hemocompatibility, with a prolonged clotting time, inhibited platelets adhesion as well as reduced hemolysis compared to untreated Mg. In addition, both PA&Hep and PA&BVLD coatings promoted endothelial cells growth and restrained the proliferation of smooth muscle cells. In vivo assays indicated that PA&Hep-coated Mg exhibited a significant difference in mass loss compared to untreated Mg, as well as better histocompatibility than other samples. These results demonstrate that our coating strategy shows a great potential in surface modification of biodegradable Mg. Finally, the mechanism for the incorporation of the drugs into the PA coating is discussed from both theoretical and practical perspectives.